2010
DOI: 10.1016/j.biomaterials.2010.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Regulating in vivo calcification of alginate microbeads

Abstract: Alginate calcification has been previously reported clinically and during animal implantation; however no study has investigated the mechanism, extensively characterized the mineral, or evaluated multiple methods to regulate or eliminate mineralization. In the present study, alginate calcification was first studied in vitro: calcium-crosslinked alginate beads sequestered surrounding phosphate while forming traces of hydroxyapatite. Calcification in vivo was then examined in nude mice using alginate microbeads … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 40 publications
1
36
0
Order By: Relevance
“…Further, it has been reported that presentation of RGD tripeptide to alginate scaffold can promote osteoblast proliferation, leading to increased bone regeneration capacity. 24,28 In our current in vitro study, we confirmed that RGD-modified alginate microspheres containing dental MSCs indeed produced significantly more mineralized tissue than was generated by unmodified alginate hydrogel.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Further, it has been reported that presentation of RGD tripeptide to alginate scaffold can promote osteoblast proliferation, leading to increased bone regeneration capacity. 24,28 In our current in vitro study, we confirmed that RGD-modified alginate microspheres containing dental MSCs indeed produced significantly more mineralized tissue than was generated by unmodified alginate hydrogel.…”
Section: Discussionsupporting
confidence: 70%
“…25,26 Due to their unique properties including gentle gelation behavior, biodegradability, biocompatibility, easy cell encapsulation/cell recovery, and chemical versatility, they have a wide variety of biomedical applications, such as the encapsulation of cells and sensitive bioactive molecules to facilitate minimally invasive surgical procedures. [27][28][29] In our previous studies, we have utilized alginate hydrogels as a scaffold for the encapsulation of PDLSCs and GMSCs. 19,20 We showed that an alginate encapsulation system has the potential to enhance hard tissue regeneration in vitro and in vivo, making it a promising candidate for minimally invasive dental and orthopedic applications.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, calcium-cross-linked alginate calcifies through binding the surrounding phosphate ions to form calcium phosphate crystals. These crystals are stable in neutral to basic environments and do not appear at pH of less than 6.8 (Lee et al, 2010). We believe that the calcified constructs were possibly generated in a neutral to alkaline environment prior to implantation, since these constructs were either not metabolically active (non-seeded alginate) or had a low metabolic activity due to stable cartilage formation (ACs) or due to the deficiency of TGFβ1.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, alginate has been used for bone regeneration, considering its calcification capacity in vivo. This results from interactions between Ca 2+ in the cross-linked alginate and the surrounding phosphate ions [101], making it a useful base material for orthopedic applications. However, the slow and uncontrolled degradation in vivo and poor cell adhesion properties of alginate must be addressed [102].…”
Section: Injectable Microspheres For Tissue Engineeringmentioning
confidence: 99%